Perspective of radiography science – a document analysis of dissertations - Törnroos, Sanna (John Wiley & Sons, 2026)
Introduction: The aim of this study was to clarify the perspective of radiography science as an academic discipline. A discipline can be studied by discovering the collective use of concepts, especially core concepts. We have previously identified the core concepts as clinical practices in radiography, radiographers' profession, safe and high-quality radiation use, and technology in radiography. The relationships between these concepts have not been studied previously. In order to clarify the perspective of radiography science we have investigated further the core concepts, their interrelationships and interdependencies.
Methods: Altogether, 53 dissertations meeting the inclusion criteria were selected for a qualitative document analysis. The data were first analysed deductively using an extraction matrix comprising four core concepts developed from previous studies, then relational statements were synthesised, and the statements were analysed semantically.
Results: Analysis revealed the bilateral interrelationships between the concepts and their dependencies. All the concepts were used within healthcare. The rationale for radiography science research was the clinical practice of radiography and the improvement of services in a complex environment as a part of patients' pathways. Safe and high-quality radiation use was investigated as a means to deliver optimal services. Technology was studied as being functional or a means to deliver services. The perspective of the discipline was seen as the combination of humanistic interaction with advanced technology, where safety and quality were a necessity.
Conclusions: Defining core concepts and their interrelations clarifies the perspective of the discipline and gives radiography researchers a way to argue their viewpoint.